Scaleable ultra-thin and high power density graphene electrochemical capacitor electrodes manufactured by aqueous exfoliation and spray deposition - MENDOZA SANCHEZ, BEATRIZ; NICOLOSI, VALERIA (My University, 2013)
Graphene electrodes of high power density were manufactured by a surfactant-water based exfoliation method followed by a scaleable spray-deposition process. Cyclic voltammetry and galvanostatic charge–discharge experiments revealed a combination of electric double layer and pseudocapacitive behavior that, unlike the many graphene-oxide derived electrodes, was maintained to unusually high scan rates of 10,000 mV s−1, reaching a maximum capacitance of 543 μF cm−2 and with a capacitive retention of 57% at 10,000 mV s−1. The performance of graphene electrodes was contrasted with carboxylated single walled carbon nanotubes that showed a sharp decrease in capacitance above 200 mV s−1. Electrochemical impedance spectroscopy analysis showed a fast capacitor response of 17.4 ms for as manufactured electrodes which was further improved to 2.3 ms for surfactant-free 40 nm thick electrodes. A maximum energy density of 75.4 nW h cm−2 gradually decreased as power density increased up to 2.6 mW cm−2. Graphene electrodes showed 100% capacitance retention for 5000 cycles at the high power scan rate of 10,000 mV s−1.
PUBLISHED
Keywords: Graphene